"La libellula": At the Origins of Amelia Rosselli’s Experimentation (inOpera Esercizi di lettura su testi contemporanei, 2024)
The contribution intends to dedicate ample space to the critical interpretation of one of Amelia Rosselli's earliest and most significant works, the long poem entitled La libellula, to which the author remained particularly attached throughout the entire course of her poetic activity. A brief introduction aimed at clarifying the importance of the poem within Rosselli's poetic trajectory is followed by a commentary that seeks to highlight its main content and formal aspects; furthermore, particular attention is paid to the dense inter-textual dialogue established by the author with some of the protagonists of the Italian and other literary traditions.
Keywords: Amelia Rosselli; La libellula; Intertextuality; Long Poem; Literary Tradition